Empowering Higher Education Through Digital Transformation and Strategic Planning for Academic Advancement - Al-Shamsi, Ibrahim Rashid (Emerging Science Journal, 2024)
The digitalization of strategic planning is crucial for Oman's postsecondary higher education. This study focuses on the impact of automating and digitalizing strategic planning management to bridge gaps and improve decision-making. Aligning strategies with goals through digitalization enhances academic excellence and global recognition, providing valuable insights for Omani higher education managers. Investigating strategic planning automation in non-Western settings, it advocates for integrating digital tools to advance academia globally. The main objective is to assess how automation and digital information affect these institutions' effectiveness, accuracy, and efficiency in strategic planning. Structural Equation Modeling (SEM) used as the primary methodology. The dataset consists of 224 participants and 15 indicators. Both the measurement model and structural model were employed for analysis and testing. The results show that a two-tailed test with t=-1.96 at a 95% significance level found automation significantly affects strategic planning (B=0.36, t=2.97, p=0.000), and digitalization significantly affects strategic planning (B=0.30, t=2.68, p=0.01). Mediation analysis of automation as a mediator revealed a noteworthy indirect relationship between digitalization and effective strategic planning (B=0.30, t=2.96, p=0.000). While automation offers many advantages, digitalization enables a more comprehensive and fundamental change that supports various strategic goals. By integrating digitalization into their strategic planning, organizations can create a robust digital infrastructure that improves data capabilities, encourages innovation, and boosts agility, providing a sense of security about the future of Omani higher education. This positions them for long-term success and resilience in the face of changes in the business environment. Doi: 10.28991/ESJ-2024-SIED1-019 Full Text: PDF